(3OjhGf GHf MeOjS GdUbdjs - (3YHO GdLHGQ Hf CHj HcQ Hf eMeO Hf MeOjS GdCROj GdUbdj, CHh eMeO,J (B527 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhj s)
(3ChdgG (B:s
(3HYO GdHSedI(B: (3bGajI GdgeRI hGdCda(B: (3bGd GdTjN GdaGVd Edi eJi efce gLQj hEbUGFj hrjdj, hrLOoJ CMHGFj cCYOGFj s
(3BNQgG (B:s
(3SeYJ ebGdI TjNj GdfUjM hOGQj Yf OGQg fGFjg acGfJ dCrPfj HgG UQNI CQGO HgG oYeQ SGQjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdOjhGf eQJH Ydi MQha GdeYLes
(3jdjg bhGa oCZadJ hJdMb aj ecGfgG JHOC aj hQbI (B85 (3Hs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B47 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B79s
Keywords: (3GdCOHs